Mineralogy of Iron Microbial Mats from Loihi Seamount - Toner, Brandy M.; Berquó, Thelma S.; Michel, F. Marc; Sorensen, Jeffry V.; Templeton, Alexis S.; Edwards, Katrina J. (Frontiers in Microbiology, 2012)
Extensive mats of Fe oxyhydroxides and associated Fe-oxidizing microbial organisms form in diverse geochemical settings – freshwater seeps to deep-sea vents – where ever opposing Fe(II)-oxygen gradients prevail. The mineralogy, reactivity, and structural transformations of Fe oxyhydroxides precipitated from submarine hydrothermal fluids within microbial mats remains elusive in active and fossil systems. In response, a study of Fe microbial mat formation at the Loihi Seamount was conducted to describe the physical and chemical characteristics of Fe-phases using extended X-ray absorption fine structure spectroscopy, powder X-ray diffraction, synchrotron radiation X-ray total scattering, low-temperature magnetic measurements, and Mössbauer spectroscopy. Particle sizes of 3.5–4.6 nm were estimated from magnetism data, and coherent scattering domain (CSD) sizes as small as 1.6 nm are indicated by pair distribution function (PDF) analysis. Disorder in the nanostructured Fe-bearing phases results in limited intermediate-range structural order: less than that of standard two-line ferrihydrite (Fh), except for the Pohaku site. The short-range ordered natural Fh (FhSRO) phases were stable at 4°C in the presence of oxygen for at least 1 year and during 400°C treatment. The observed stability of the FhSRO is consistent with magnetic observations that point to non-interacting nanoparticles. PDF analyses of total scattering data provide further evidence for FhSRO particles with a poorly ordered silica coating. The presence of coated particles explains the small CSD for the mat minerals, as well as the stability of the minerals over time and against heating. The mineral properties observed here provide a starting point from which progressively older and more extensively altered Fe deposits may be examined, with the ultimate goal of improved interpretation of past biogeochemical conditions and diagenetic processes.